Large-size anti-falling rock plate adhesive and preparation method thereof

By using raw materials and treatment methods with specific ratios, a large-scale anti-falling rock sheet adhesive was prepared, which solved the difficulty of coordinated improvement of anti-falling performance, compressive strength and shrinkage rate of rock sheet adhesive in the prior art. The problem of achieving higher heat-freezing cycle resistance and water immersion stability.

CN119430808AActive Publication Date: 2025-02-14GUANGDONG HERUI INTELLIGENT MFG NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411741614.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The anti-falling performance, compressive strength and shrinkage of existing large-size rock slab adhesives are difficult to coordinate and improve, and the heat-freezing cycle resistance and water immersion stability are poor, which affects the use efficiency.

Method used

Using silicate cement, river sand, silicon powder, anti-falling functional agent, basalt fiber agent based on coal gangue doping and yttrium blending agent, a large-scale anti-prevention is prepared through specific ratios and treatment methods. Remove the rock plate adhesive.

Benefits of technology

It significantly improves the anti-falling, compressive strength and shrinkage performance of rock slab adhesive, improves the heat-freezing cycle and water immersion stability, and improves the use efficiency of rock slabs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162722740000131
    Figure BDA0005162722740000131
  • Figure BDA0005162722740000141
    Figure BDA0005162722740000141
  • Figure BDA0005162722740000161
    Figure BDA0005162722740000161
Patent Text Reader

Abstract

The invention discloses a large-size anti-falling rock plate adhesive and a preparation method thereof. The rock plate adhesive comprises the following raw materials in parts by weight: 50-60 parts of Portland cement, 35-40 parts of river sand with the particle size of 0.2 mm, 5-8 parts of silicon powder, 6-9 parts of an anti-falling functional agent, 5-8 parts of a basalt fiber agent based on coal gangue blending, 4-7 parts of an yttrium blender, 2-5 parts of a water reducing agent and 40-50 parts of water. The Portland cement and the river sand with the particle size of 0.2 mm are used as base materials, the water reducing agent is added to serve as a functional additive, the added silicon powder has an active adding effect, and the added anti-falling functional agent and the basalt fiber based on coal gangue blending are matched and coordinated, so that the performance effect of a system is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rock slab adhesives, and in particular to a large-scale anti-falling rock slab adhesive and a preparation method thereof. Background Art

[0002] The rock slab is made of natural raw materials through a special process, using a press with a capacity of more than 10,000 tons and fired at high temperature. It can be cut, drilled, polished and other processing. It is a new type of ceramic material with extra-large specifications.

[0003] Existing large-sized rock slabs need to be bonded to the wall. Due to the large size and heavy weight of the rock slabs, the adhesive used has poor anti-falling bonding performance. At the same time, the shrinkage rate and compressive strength of the product are difficult to improve in a coordinated manner, and the product has poor resistance to heat-freeze cycles and water immersion stability, which easily affects the use efficiency of the rock slabs. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a large-scale anti-falling rock slab adhesive and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a large-scale anti-falling rock plate adhesive, which includes the following raw materials in parts by weight:

[0007] 50-60 parts of Portland cement, 35-40 parts of river sand with a particle size of 0.2 mm, 5-8 parts of silica fume, 6-9 parts of anti-shedding functional agent, 5-8 parts of basalt fiber agent based on coal gangue, 4-7 parts of yttrium blending agent, 2-5 parts of water reducing agent, and 40-50 parts of water;

[0008] The preparation method of yttrium conditioning agent is:

[0009] 3 to 5 parts of 2 to 5% by mass yttrium nitrate solution and 1 to 3 parts of nano-silica sol are mixed and added into 6 to 10 parts of 5% by mass sodium dodecylbenzene sulfonate solution, and stirred and mixed thoroughly to obtain a yttrium conditioning agent.

[0010] Preferably, the water reducer is a polycarboxylate water reducer; and the particle size of the silica powder is 10 to 20 nm.

[0011] Preferably, the preparation method of the anti-shedding functional agent is:

[0012] S01: 2 to 5 parts of silane coupling agent KH560, 4 to 6 parts of 5% by mass sodium citrate solution and 1 to 3 parts of ethanol are mixed to obtain a coupling modification liquid;

[0013] S02: 4-7 parts of flake boron nitride and 2-5 parts of silicon carbide are mixed and added into the coupling modification liquid, and stirred and mixed thoroughly to obtain a composite modification agent;

[0014] S03: adding 10-15% of the total amount of the composite modifier to the composite modifier, and stirring the mixture. After the stirring is completed, washing, filtering, and drying are performed to obtain an anti-shedding functional agent.

[0015] Preferably, the stirring temperature of the stirring treatment in S03 is 50-55° C., the stirring speed is 350-400 r / min, and the stirring time is 20-30 min.

[0016] Preferably, the preparation method of the basalt fiber agent based on coal gangue blending is:

[0017] S11: Stir and mix the coal gangue thoroughly in a sufficient amount of potassium permanganate solution with a mass fraction of 2 to 5%, then wash, filter and dry;

[0018] S12: immersing the dried coal gangue in an ethanol / water solution of 3 to 5 times the total amount of the dried coal gangue, and stirring the solution thoroughly, wherein the ethanol / water solution is prepared by mixing ethanol and water in a weight ratio of 7:3;

[0019] Then, add 5-8% of the total amount of the gangue of the S12 silane coupling agent KH550, continue to stir fully, and finally wash and dry to obtain pre-adjusted gangue;

[0020] S13: The pre-adjusted coal gangue and basalt fiber blending agent are mixed and ball-milled in a weight ratio of 5:(2-3). After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a basalt fiber agent based on coal gangue blending.

[0021] Preferably, the ball milling speed of the mixing ball milling treatment in S13 is 550-750 r / min, and the ball milling is performed for 2 hours.

[0022] Preferably, the preparation method of the basalt fiber admixture is:

[0023] 3-5 parts of basalt fiber, 1-3 parts of 5% sodium silicate solution by mass and 2-4 parts of 3-4% lanthanum chloride solution by mass are mixed and ball-milled at a ball-milling speed of 1000 r / min for 1 hour to obtain a basalt fiber modifier;

[0024] Add 1 to 3 parts of calcium dodecylbenzene sulfonate to 2 to 5 parts of dopamine hydrochloride solution and mix thoroughly to obtain a treatment agent; continue to mix the halloysite powder and the treatment agent thoroughly at a weight ratio of 2:5, then wash with water, filter and dry to obtain a halloysite agent;

[0025] The halloysite agent and the basalt fiber modifier are subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment is completed, a basalt fiber admixture is obtained.

[0026] Preferably, the mass fraction of the dopamine hydrochloride solution is 10-15%; the length of the halloysite powder is 2-5 um.

[0027] Preferably, the ultrasonic power of the ultrasonic modification treatment is 350-400 W, and the ultrasonic time is 20-30 min.

[0028] The present invention also provides a method for preparing a large-scale anti-falling rock plate adhesive, comprising the following steps:

[0029] Adding silicon powder, anti-shedding functional agent, and basalt fiber agent based on coal gangue into yttrium blending agent, stirring sufficiently, and then filtering and drying to obtain additives;

[0030] The additive, silicate cement, river sand with a particle size of 0.2 mm, a water reducer and water are further mixed to obtain the large-scale anti-falling rock slab adhesive of the present invention.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The silicate cement and river sand with a particle size of 0.2 mm are used as the matrix material, a water reducer is added as a functional additive, and the added silicon powder has an active addition effect. When added to the system, the active connectivity between the raw materials is enhanced, and the compactness of the system is improved. The silicon powder with a nanostructure is easy to agglomerate, so it is first treated with a yttrium conditioning agent, and the yttrium nitrate solution, nano-silica sol and sodium dodecylbenzene sulfonate solution in the yttrium conditioning agent are synergistically prepared. The yttrium nitrate solution in the yttrium conditioning agent is synergistically prepared to enhance the activity of the system, and the nano-silica sol is used to treat the yttrium nitrate solution. Sol and sodium dodecylbenzene sulfonate solution are co-dispersed to enhance the role of silicon powder in the system, and the added anti-shedding functional agent and basalt fiber agent based on coal gangue are co-coordinated to improve the anti-shedding property and performance stability of the product, and further enhance the performance effect of the system; the anti-shedding functional agent adopts silane coupling agent and is fully mixed with sodium citrate solution and ethanol to obtain a coupling modified liquid, and at the same time, flake boron nitride and silicon carbide are blended and added to the coupling modified liquid, stirred and mixed thoroughly, and then adjusted with chitosan solution. The basalt fiber agent based on coal gangue blending is made by treating coal gangue with potassium permanganate solution, and then immersing and stirring it in ethanol / water solution and silane coupling agent KH550 to optimize the active effect of coal gangue in the system and better fill it into the system. Basalt fiber is used as a matrix material, reinforced with a needle-like structure, and mixed with a sodium silicate solution with a mass fraction of 5% and a lanthanum chloride solution with a mass fraction of 3-4%. The raw materials are harmonized and coordinated, and then calcium dodecylbenzene sulfonate is added to the dopamine hydrochloride solution to fully blend to obtain a treating agent. The halloysite agent obtained by combining the treating agent with the improved halloysite powder is further used to improve the basalt fiber modifier, so that the obtained basalt fiber admixture is better coordinated with the coal gangue, thereby further improving the performance. DETAILED DESCRIPTION

[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] A large-scale anti-falling rock plate adhesive of this embodiment includes the following raw materials in parts by weight:

[0035] 50-60 parts of Portland cement, 35-40 parts of river sand with a particle size of 0.2 mm, 5-8 parts of silica fume, 6-9 parts of anti-shedding functional agent, 5-8 parts of basalt fiber agent based on coal gangue, 4-7 parts of yttrium blending agent, 2-5 parts of water reducing agent, and 40-50 parts of water;

[0036] The preparation method of yttrium conditioning agent is:

[0037] 3 to 5 parts of 2 to 5% by mass yttrium nitrate solution and 1 to 3 parts of nano-silica sol are mixed and added into 6 to 10 parts of 5% by mass sodium dodecylbenzene sulfonate solution, and stirred and mixed thoroughly to obtain a yttrium conditioning agent.

[0038] The water reducing agent in this embodiment is a polycarboxylic acid water reducing agent; the particle size of the silicon powder is 10 to 20 nm.

[0039] The preparation method of the anti-shedding functional agent of this embodiment is:

[0040] S01: 2 to 5 parts of silane coupling agent KH560, 4 to 6 parts of 5% by mass sodium citrate solution and 1 to 3 parts of ethanol are mixed to obtain a coupling modification liquid;

[0041] S02: 4-7 parts of flake boron nitride and 2-5 parts of silicon carbide are mixed and added into the coupling modification liquid, and stirred and mixed thoroughly to obtain a composite modification agent;

[0042] S03: adding 10-15% of the total amount of the composite modifier to the composite modifier, and stirring the mixture. After the stirring is completed, washing, filtering, and drying are performed to obtain an anti-shedding functional agent.

[0043] The stirring temperature of the stirring treatment in S03 of this embodiment is 50-55° C., the stirring speed is 350-400 r / min, and the stirring time is 20-30 min.

[0044] The preparation method of the basalt fiber agent based on coal gangue blending in this embodiment is as follows:

[0045] S11: Stir and mix the coal gangue thoroughly in a sufficient amount of potassium permanganate solution with a mass fraction of 2 to 5%, then wash, filter and dry;

[0046] S12: immersing the dried coal gangue in an ethanol / water solution of 3 to 5 times the total amount of the dried coal gangue, and stirring the solution thoroughly, wherein the ethanol / water solution is prepared by mixing ethanol and water in a weight ratio of 7:3;

[0047] Then, add 5-8% of the total amount of the gangue of the S12 silane coupling agent KH550, continue to stir fully, and finally wash and dry to obtain pre-adjusted gangue;

[0048] S13: The pre-adjusted coal gangue and basalt fiber blending agent are mixed and ball-milled in a weight ratio of 5:(2-3). After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a basalt fiber agent based on coal gangue blending.

[0049] The ball milling speed of the mixing ball milling treatment in S13 of this embodiment is 550-750 r / min, and the ball milling is performed for 2 hours.

[0050] The preparation method of the basalt fiber admixture of this embodiment is as follows:

[0051] 3-5 parts of basalt fiber, 1-3 parts of 5% sodium silicate solution by mass and 2-4 parts of 3-4% lanthanum chloride solution by mass are mixed and ball-milled at a ball-milling speed of 1000 r / min for 1 hour to obtain a basalt fiber modifier;

[0052] Add 1 to 3 parts of calcium dodecylbenzene sulfonate to 2 to 5 parts of dopamine hydrochloride solution and mix thoroughly to obtain a treatment agent; continue to mix the halloysite powder and the treatment agent thoroughly at a weight ratio of 2:5, then wash with water, filter and dry to obtain a halloysite agent;

[0053] The halloysite agent and the basalt fiber modifier are subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment is completed, a basalt fiber admixture is obtained.

[0054] The mass fraction of the dopamine hydrochloride solution in this embodiment is 10-15%; the length of the halloysite powder is 2-5 um.

[0055] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350-400 W, and the ultrasonic time is 20-30 min.

[0056] The method for preparing a large-scale anti-falling rock plate adhesive of this embodiment includes the following steps:

[0057] Adding silicon powder, anti-shedding functional agent, and basalt fiber agent based on coal gangue into yttrium blending agent, stirring sufficiently, and then filtering and drying to obtain additives;

[0058] The additive, silicate cement, river sand with a particle size of 0.2 mm, a water reducer and water are further mixed to obtain the large-scale anti-falling rock slab adhesive of the present invention.

[0059] Example 1.

[0060] A large-scale anti-falling rock plate adhesive of this embodiment includes the following raw materials in parts by weight:

[0061] 50 parts of Portland cement, 35 parts of river sand with a particle size of 0.2 mm, 5 parts of silica fume, 6 parts of anti-shedding functional agent, 5 parts of basalt fiber agent based on coal gangue, 4 parts of yttrium blending agent, 2 parts of water reducing agent, and 40 parts of water;

[0062] The preparation method of yttrium conditioning agent is:

[0063] 3 parts of 2% by mass yttrium nitrate solution and 1 part of nano-silica sol are mixed and added into 6 parts of 5% by mass sodium dodecylbenzene sulfonate solution, and stirred and mixed thoroughly to obtain a yttrium conditioning agent.

[0064] The water reducer in this embodiment is a polycarboxylic acid water reducer; the particle size of the silicon powder is 10 nm.

[0065] The preparation method of the anti-shedding functional agent of this embodiment is:

[0066] S01: 2 parts of silane coupling agent KH560, 4 parts of 5% by mass sodium citrate solution and 1 part of ethanol are mixed to obtain a coupling modification liquid;

[0067] S02: 4 parts of flake boron nitride and 2 parts of silicon carbide are mixed and added into the coupling modification liquid, and stirred to mix well to obtain a composite modification agent;

[0068] S03: adding 5% by mass of chitosan solution, which is 10% of the total amount of the composite modifier, to the composite modifier and stirring, after stirring, washing, filtering and drying to obtain an anti-shedding functional agent.

[0069] The stirring temperature of the stirring treatment in S03 of this embodiment is 50° C., the stirring speed is 350 r / min, and the stirring time is 20 min.

[0070] The preparation method of the basalt fiber agent based on coal gangue blending in this embodiment is as follows:

[0071] S11: Stir and mix the coal gangue in a sufficient amount of 2% by mass potassium permanganate solution, then wash, filter and dry;

[0072] S12: immersing the dried coal gangue in an ethanol / water solution of 3 times the total amount of the dried coal gangue, and stirring the solution thoroughly, wherein the ethanol / water solution is prepared by mixing ethanol and water in a weight ratio of 7:3;

[0073] Then, add 5% of the total amount of silane coupling agent KH550 to the coal gangue of S12, continue to stir fully, and finally wash and dry to obtain pre-adjusted coal gangue;

[0074] S13: The pre-adjusted coal gangue and basalt fiber blending agent are mixed in a weight ratio of 5:2 and subjected to ball milling. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a basalt fiber agent based on coal gangue blending.

[0075] The ball milling speed of the mixing ball milling treatment in S13 of this embodiment is 5500 r / min, and the ball milling is performed for 2 hours.

[0076] The preparation method of the basalt fiber admixture of this embodiment is as follows:

[0077] 3 parts of basalt fiber, 1 part of 5% by mass sodium silicate solution and 2 parts of 3% by mass lanthanum chloride solution were mixed and ball-milled at a ball-milling speed of 1000 r / min for 1 hour to obtain a basalt fiber modifier;

[0078] Add 1 part of calcium dodecylbenzene sulfonate to 2 parts of dopamine hydrochloride solution and mix thoroughly to obtain a treatment agent; continue to mix the halloysite powder and the treatment agent thoroughly at a weight ratio of 2:5, then wash with water, filter and dry to obtain a halloysite agent;

[0079] The halloysite agent and the basalt fiber modifier are subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment is completed, a basalt fiber admixture is obtained.

[0080] The mass fraction of the dopamine hydrochloride solution in this embodiment is 10%; the length of the halloysite powder is 2 um.

[0081] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350W, and the ultrasonic time is 20min.

[0082] The method for preparing a large-scale anti-falling rock plate adhesive of this embodiment includes the following steps:

[0083] Adding silicon powder, anti-shedding functional agent, and basalt fiber agent based on coal gangue into yttrium blending agent, stirring sufficiently, and then filtering and drying to obtain additives;

[0084] The additive, silicate cement, river sand with a particle size of 0.2 mm, a water reducer and water are further mixed to obtain the large-scale anti-falling rock slab adhesive of the present invention.

[0085] Example 2.

[0086] A large-scale anti-falling rock plate adhesive of this embodiment includes the following raw materials in parts by weight:

[0087] 60 parts of Portland cement, 40 parts of river sand with a particle size of 0.2 mm, 8 parts of silica fume, 9 parts of anti-shedding functional agent, 8 parts of basalt fiber agent based on coal gangue, 7 parts of yttrium blending agent, 5 parts of water reducing agent, and 50 parts of water;

[0088] The preparation method of yttrium conditioning agent is:

[0089] 5 parts of 5% by mass yttrium nitrate solution and 3 parts of nano-silica sol are mixed and added into 10 parts of 5% by mass sodium dodecylbenzene sulfonate solution, and stirred and mixed thoroughly to obtain a yttrium conditioning agent.

[0090] The water reducing agent in this embodiment is a polycarboxylic acid water reducing agent; the particle size of the silicon powder is 20 nm.

[0091] The preparation method of the anti-shedding functional agent of this embodiment is:

[0092] S01: 5 parts of silane coupling agent KH560, 6 parts of 5% by mass sodium citrate solution and 3 parts of ethanol are mixed to obtain a coupling modified liquid;

[0093] S02: 7 parts of flake boron nitride and 5 parts of silicon carbide are mixed and added into the coupling modification liquid, and stirred to mix well to obtain a composite modification agent;

[0094] S03: adding 5% by mass of chitosan solution, which is 15% of the total amount of the composite modifier, to the composite modifier and stirring, after stirring, washing, filtering and drying to obtain an anti-shedding functional agent.

[0095] The stirring temperature of the stirring treatment in S03 of this embodiment is 55° C., the stirring speed is 400 r / min, and the stirring time is 30 min.

[0096] The preparation method of the basalt fiber agent based on coal gangue blending in this embodiment is as follows:

[0097] S11: Stir and mix the coal gangue in a sufficient amount of 5% by mass potassium permanganate solution, then wash, filter and dry;

[0098] S12: immersing the dried coal gangue in an ethanol / water solution of 5 times the total amount of the dried coal gangue, and stirring the solution thoroughly, wherein the ethanol / water solution is prepared by mixing ethanol and water in a weight ratio of 7:3;

[0099] Then add silane coupling agent KH550 in an amount of 8% of the total amount of the coal gangue to the coal gangue of S12, continue to stir fully, and finally wash and dry to obtain pre-adjusted coal gangue;

[0100] S13: The pre-adjusted coal gangue and basalt fiber blending agent are mixed in a weight ratio of 5:3 and ball-milled. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a basalt fiber agent based on coal gangue blending.

[0101] The ball milling speed of the mixing ball milling treatment in S13 of this embodiment is 750 r / min, and the ball milling is performed for 2 hours.

[0102] The preparation method of the basalt fiber admixture of this embodiment is as follows:

[0103] 5 parts of basalt fiber, 3 parts of 5% sodium silicate solution by mass and 4 parts of 4% lanthanum chloride solution by mass were mixed and ball-milled at a ball-milling speed of 1000 r / min for 1 hour to obtain a basalt fiber modifier;

[0104] Add 3 parts of calcium dodecylbenzene sulfonate to 5 parts of dopamine hydrochloride solution and mix thoroughly to obtain a treatment agent; continue to mix the halloysite powder and the treatment agent thoroughly at a weight ratio of 2:5, then wash with water, filter and dry to obtain a halloysite agent;

[0105] The halloysite agent and the basalt fiber modifier are subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment is completed, a basalt fiber admixture is obtained.

[0106] The mass fraction of the dopamine hydrochloride solution in this embodiment is 15%; the length of the halloysite powder is 5 um.

[0107] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.

[0108] The method for preparing a large-scale anti-falling rock plate adhesive of this embodiment includes the following steps:

[0109] Adding silicon powder, anti-shedding functional agent, and basalt fiber agent based on coal gangue into yttrium blending agent, stirring sufficiently, and then filtering and drying to obtain additives;

[0110] The additive, silicate cement, river sand with a particle size of 0.2 mm, a water reducer and water are further mixed to obtain the large-scale anti-falling rock slab adhesive of the present invention.

[0111] Example 3.

[0112] A large-scale anti-falling rock plate adhesive of this embodiment includes the following raw materials in parts by weight:

[0113] 55 parts of Portland cement, 37.5 parts of river sand with a particle size of 0.2 mm, 6.5 parts of silica fume, 7.5 parts of anti-shedding functional agent, 6.5 parts of basalt fiber agent based on coal gangue, 5.5 parts of yttrium blending agent, 3.5 parts of water reducing agent, and 45 parts of water;

[0114] The preparation method of yttrium conditioning agent is:

[0115] 4 parts of 3.5% by mass yttrium nitrate solution and 2 parts of nano-silica sol are mixed and added into 8 parts of 5% by mass sodium dodecylbenzene sulfonate solution, and stirred and mixed thoroughly to obtain a yttrium conditioning agent.

[0116] The water reducing agent in this embodiment is a polycarboxylic acid water reducing agent; the particle size of the silicon powder is 15 nm.

[0117] The preparation method of the anti-shedding functional agent of this embodiment is:

[0118] S01: 3.5 parts of silane coupling agent KH560, 5 parts of 5% by mass sodium citrate solution and 2 parts of ethanol are mixed to obtain a coupling modified liquid;

[0119] S02: 5.5 parts of flake boron nitride and 3.5 parts of silicon carbide are mixed and added into the coupling modification liquid, and stirred and mixed thoroughly to obtain a composite modification agent;

[0120] S03: adding 5% chitosan solution with a mass fraction of 12.5% ​​of the total amount of the composite modifier to the composite modifier and stirring, after stirring, washing, filtering and drying to obtain an anti-shedding functional agent.

[0121] The stirring temperature of the stirring treatment in S03 of this embodiment is 52° C., the stirring speed is 370 r / min, and the stirring time is 25 min.

[0122] The preparation method of the basalt fiber agent based on coal gangue blending in this embodiment is as follows:

[0123] S11: Stir the coal gangue in a sufficient amount of 3.5% by mass potassium permanganate solution to mix thoroughly, then wash, filter and dry;

[0124] S12: immersing the dried coal gangue in an ethanol / water solution of 4 times the total amount of the dried coal gangue, and stirring the solution thoroughly, wherein the ethanol / water solution is prepared by mixing ethanol and water in a weight ratio of 7:3;

[0125] Then, add 5-8% of the total amount of the gangue of the S12 silane coupling agent KH550, continue to stir fully, and finally wash and dry to obtain pre-adjusted gangue;

[0126] S13: The pre-adjusted coal gangue and basalt fiber blending agent are mixed and ball-milled in a weight ratio of 2:1. After the ball-milling is completed, the mixture is washed, filtered and dried to obtain a basalt fiber agent based on coal gangue blending.

[0127] The ball milling speed of the mixing ball milling treatment in S13 of this embodiment is 600 r / min, and the ball milling is performed for 2 hours.

[0128] The preparation method of the basalt fiber admixture of this embodiment is as follows:

[0129] 4 parts of basalt fiber, 2 parts of 5% sodium silicate solution and 3 parts of 3.5% lanthanum chloride solution were mixed and ball-milled at a speed of 1000 r / min for 1 h to obtain a basalt fiber modifier.

[0130] Add 2 parts of calcium dodecylbenzene sulfonate to 3.5 parts of dopamine hydrochloride solution and mix thoroughly to obtain a treatment agent; continue to mix the halloysite powder and the treatment agent thoroughly at a weight ratio of 2:5, then wash with water, filter and dry to obtain a halloysite agent;

[0131] The halloysite agent and the basalt fiber modifier are subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment is completed, a basalt fiber admixture is obtained.

[0132] The mass fraction of the dopamine hydrochloride solution in this embodiment is 12.5%; the length of the halloysite powder is 3.5 um.

[0133] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 370W, and the ultrasonic time is 25min.

[0134] The method for preparing a large-scale anti-falling rock plate adhesive of this embodiment includes the following steps:

[0135] Adding silicon powder, anti-shedding functional agent, and basalt fiber agent based on coal gangue into yttrium blending agent, stirring sufficiently, and then filtering and drying to obtain additives;

[0136] The additive, silicate cement, river sand with a particle size of 0.2 mm, a water reducer and water are further mixed to obtain the large-scale anti-falling rock slab adhesive of the present invention.

[0137] Comparative Example 1.

[0138] The difference from Example 3 is that no anti-shedding functional agent is added.

[0139] Comparative Example 2.

[0140] The difference from Example 3 is that step S03 is not used in the preparation of the anti-shedding functional agent.

[0141] Comparative Example 3.

[0142] The difference from Example 3 is that no coupling modification liquid treatment is used in the preparation of the anti-shedding functional agent.

[0143] Comparative Example 4.

[0144] The difference from Example 3 is that silicon carbide is not added in the preparation of the anti-shedding functional agent.

[0145] Comparative Example 5.

[0146] The difference from Example 3 is that the basalt fiber agent based on coal gangue blending is not added.

[0147] Comparative Example 6.

[0148] The difference from Example 3 is that the pre-adjusted coal gangue in the preparation of the basalt fiber agent based on coal gangue is replaced by coal gangue.

[0149] Comparative Example 7.

[0150] The difference from Example 3 is that basalt fiber blending agent treatment is not used in the preparation of basalt fiber agent based on coal gangue blending.

[0151] Comparative Example 8.

[0152] The difference from Example 3 is that no yttrium conditioning agent treatment is used.

[0153] Comparative Example 9.

[0154] The difference from Example 3 is that no yttrium nitrate solution and nano-silica sol are added to the yttrium conditioning agent.

[0155] Conventional tests, compressive strength, tensile bonding strength and shrinkage performance of Examples 1 to 3 and Comparative Examples 1 to 9, were tested according to JC / T547-2017 standard;

[0156]

[0157] It can be seen from Comparative Examples 1 to 9 and Examples 1 to 3 that;

[0158] The product of Example 3 has excellent 28d compressive strength, and the tensile bonding original strength and shrinkage performance of the product are remarkable. The compressive strength, tensile bonding original strength and shrinkage performance of the product can achieve coordinated improvement;

[0159] The products of Examples 1-3 and Comparative Examples 1-9 were coated on large-sized rock slabs of 1m.1m, and two rock slabs were bonded together with a coating thickness of 2mm for bonding treatment of the rock slabs. After maintenance at room temperature for 72 hours, the water immersion stability of the original strength of the tensile bonding of the product was tested (the rock slab was immersed in water for 72 hours, and the immersion temperature was 60°C), the heat-freeze stability cycle test (the rock slab was placed at -5°C for 24 hours, and then at 65°C for 12 hours, and the above was a cycle repeated 10 times), and the product was tested for compressive strength performance stability. The performance stability test only required the product to be immersed in water for 72 hours, and the immersion temperature was 60°C, and then taken out and dried. At the same time, the product was placed at -5°C for 24 hours, and then at 65°C for 12 hours, and the above was a cycle repeated 10 times, and the freeze-heat stability and immersion stability of the compressive strength were tested respectively;

[0160]

[0161] From comparative examples 1 to 9 and embodiment 3, it can be seen that without adding the anti-shedding functional agent, without adding the basalt fiber agent based on coal gangue blending, and without using the yttrium blending agent, the performance stability of the product has a significant trend of deterioration. The coordinated combination of the three raw materials has the most significant product performance effect.

[0162] The S03 step was not used in the preparation of the anti-shedding functional agent, the coupling modification liquid was not used in the preparation of the anti-shedding functional agent, and silicon carbide was not added in the preparation of the anti-shedding functional agent. The performance of the product also showed a trend of deterioration to varying degrees. At the same time, the pre-adjusted coal gangue in the preparation of the basalt fiber agent based on coal gangue blending was replaced by coal gangue, and the basalt fiber blending agent was not used in the preparation of the basalt fiber agent based on coal gangue blending. The performance of the product also showed a trend of deterioration. At the same time, the performance of the product was significantly deteriorated when the basalt fiber blending agent was not used. No yttrium nitrate solution and nano-silica sol were added to the yttrium blending agent, and the product performance showed a trend of deterioration. Only the raw material product obtained by the specific method of the present invention had the most significant product performance effect.

[0163] Since the performance of the product is significantly deteriorated by the addition of basalt fiber, the present invention further explores and processes it:

[0164] Experimental example 1.

[0165] The only difference from Example 3 is that no halloysite agent is added in the preparation of the basalt fiber admixture.

[0166] Experimental example 2.

[0167] The only difference from Example 3 is that no treating agent is used in the preparation of the halloysite agent.

[0168] Experimental Example 3.

[0169] The only difference from Example 3 is that calcium dodecylbenzene sulfonate is not added to the treating agent.

[0170] Experimental Example 4.

[0171] The only difference from Example 3 is that the dopamine hydrochloride solution in the treating agent is replaced by water.

[0172] Experimental Example 5.

[0173] The only difference from Example 3 is that the basalt fiber modifier was not used for treatment.

[0174] Experimental Example 6.

[0175] The only difference from Example 3 is that no basalt fiber is added in the preparation of the basalt fiber modifier.

[0176] Experimental Example 7.

[0177] The only difference from Example 3 is that no sodium silicate solution is added in the preparation of the basalt fiber modifier.

[0178] Experimental Example 8.

[0179] The only difference from Example 3 is that no lanthanum chloride solution is added in the preparation of the basalt fiber modifier. Taking the freeze-heat stability and water immersion stability tests as examples, the performance tests of Experimental Examples 1-8 are as follows:

[0180]

[0181] It can be seen from Experimental Examples 1-8 that the performance of the products showed a significant trend of deterioration when no halloysite agent was added in the preparation of the basalt fiber admixture and no basalt fiber modifier was used for treatment. The performance of the products showed a trend of deterioration to varying degrees when no basalt fiber was added in the preparation of the basalt fiber modifier, no sodium silicate solution was added in the preparation of the basalt fiber modifier, and no lanthanum chloride solution was added in the preparation of the basalt fiber modifier.

[0182] In the preparation of the halloysite agent, no treatment agent was used, calcium dodecylbenzene sulfonate was not added to the treatment agent, and water was used instead of dopamine hydrochloride solution in the treatment agent. The performance of the product also showed a trend of deterioration. The halloysite agent obtained by treating the treatment agent obtained by the specific method of the present invention and the basalt fiber modifier obtained by the specific raw materials of the present invention had the most significant product performance effect.

[0183] Only by using the basalt fiber-based admixture obtained by the specific raw materials of the present invention can the performance effect of the product be the most significant, and using other raw materials instead cannot achieve the technical effect of the present invention.

[0184] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0185] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A large-scale anti-falling rock board adhesive, characterized in that: The rock plate adhesive comprises the following raw materials in parts by weight: 50-60 parts of Portland cement, 35-40 parts of river sand with a particle size of 0.2 mm, 5-8 parts of silica fume, 6-9 parts of anti-shedding functional agent, 5-8 parts of basalt fiber agent based on coal gangue, 4-7 parts of yttrium blending agent, 2-5 parts of water reducing agent, and 40-50 parts of water; The preparation method of yttrium conditioning agent is: 3 to 5 parts of 2 to 5% by mass yttrium nitrate solution and 1 to 3 parts of nano-silica sol are mixed and added into 6 to 10 parts of 5% by mass sodium dodecylbenzene sulfonate solution, and stirred and mixed thoroughly to obtain a yttrium conditioning agent.

2. A large-scale anti-falling rock board adhesive according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer; the particle size of the silicon powder is 10 to 20 nm.

3. A large-scale anti-falling rock board adhesive according to claim 1, characterized in that: The preparation method of the anti-shedding functional agent is: S01: 2 to 5 parts of silane coupling agent KH560, 4 to 6 parts of 5% by mass sodium citrate solution and 1 to 3 parts of ethanol are mixed to obtain a coupling modification liquid; S02: 4-7 parts of flake boron nitride and 2-5 parts of silicon carbide are mixed and added into the coupling modification liquid, and stirred and mixed thoroughly to obtain a composite modification agent; S03: adding 10-15% of the total amount of the composite modifier to the composite modifier, and stirring the mixture; after stirring, washing, filtering, and drying the mixture to obtain an anti-shedding functional agent.

4. A large-scale anti-falling rock board adhesive according to claim 3, characterized in that: The stirring temperature of the stirring treatment in S03 is 50-55° C., the stirring speed is 350-400 r / min, and the stirring time is 20-30 min.

5. A large-scale anti-falling rock board adhesive according to claim 1, characterized in that: The preparation method of the basalt fiber agent based on coal gangue blending is: S11: Stir and mix the coal gangue thoroughly in a sufficient amount of potassium permanganate solution with a mass fraction of 2 to 5%, then wash, filter and dry; S12: immersing the dried coal gangue in an ethanol / water solution of 3 to 5 times the total amount of the dried coal gangue, and stirring the solution thoroughly, wherein the ethanol / water solution is prepared by mixing ethanol and water in a weight ratio of 7:3; Then, add 5-8% of the total amount of the gangue of the S12 silane coupling agent KH550, continue to stir fully, and finally wash and dry to obtain pre-adjusted gangue; S13: The pre-adjusted coal gangue and basalt fiber blending agent are mixed and ball-milled in a weight ratio of 5:(2-3). After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a basalt fiber agent based on coal gangue blending.

6. A large-scale anti-falling rock board adhesive according to claim 5, characterized in that: The ball milling speed of the mixing ball milling treatment in S13 is 550-750 r / min, and the ball milling is performed for 2 hours.

7. A large-scale anti-falling rock board adhesive according to claim 5, characterized in that: The preparation method of the basalt fiber admixture is as follows: 3-5 parts of basalt fiber, 1-3 parts of 5% sodium silicate solution by mass and 2-4 parts of 3-4% lanthanum chloride solution by mass are mixed and ball-milled at a ball-milling speed of 1000 r / min for 1 hour to obtain a basalt fiber modifier; Add 1 to 3 parts of calcium dodecylbenzene sulfonate to 2 to 5 parts of dopamine hydrochloride solution and mix thoroughly to obtain a treating agent; The halloysite powder and the treating agent are further mixed in a weight ratio of 2:5, and then washed with water, filtered, and dried to obtain a halloysite agent; The halloysite agent and the basalt fiber modifier are subjected to ultrasonic modification treatment in a weight ratio of 2:5, and after the ultrasonic treatment is completed, a basalt fiber admixture is obtained.

8. A large-scale anti-falling rock board adhesive according to claim 7, characterized in that: The mass fraction of the dopamine hydrochloride solution is 10-15%; the length of the halloysite powder is 2-5 um.

9. A large-scale anti-falling rock board adhesive according to claim 7, characterized in that: The ultrasonic power of the ultrasonic modification treatment is 350-400W, and the ultrasonic time is 20-30min.

10. A method for preparing a large-scale anti-falling rock board adhesive as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: Adding silicon powder, anti-shedding functional agent, and basalt fiber agent based on coal gangue into yttrium blending agent, stirring sufficiently, and then filtering and drying to obtain additives; The additive, silicate cement, river sand with a particle size of 0.2 mm, water reducer and water are further mixed to obtain an anti-shedding rock slab adhesive.

Citation Information

Patent Citations

  • Expansion crack water-proofing agent and using method thereof

    CN109095809A

  • Novel additive material for reducing rebound rate of tunnel wet spraying concrete

    CN116239331A

  • Two-component-based adhesive for pasting large-size ceramic tiles and preparation method of two-component-based adhesive

    CN117534396A

  • Transparent powder coating for solar panel crystalline silicon and preparation method of transparent powder coating

    CN118755334A

  • Friendly enviromental artificial rock panel using glassfiber reinforced slag and the method thereof

    KR100805912B1

Cited By

  • Coal gangue-based ceramic tile adhesive for thin-layer paving and preparation method of coal gangue-based ceramic tile adhesive

    CN120865802A

  • Coal gangue roadbed material and preparation method thereof

    CN120903894A